Frequency of Iron Deficiency Anemia in patients with Helicobacter Pylori Gastritis - Tarique Ali, Laiq Said Bacha, Fazli Rabbi, Shaista Faheem, Safia Bibi, Nowsherawan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Helicobacter pylori (H. pylori) causes worldwide infection that leads to chronic gastritis alongside multiple gastrointestinal disorders. The research shows that H. pylori increases the risk of developing iron deficiency anemia (IDA). Scientific research will determine the frequency of iron deficiency anemia (IDA) among patients suffering from H. pylori gastritis. Methods: This study was done at the Department of Medicine at Federal Govt Polyclinic Hospital Islamabad over a period of six months. Material included 228 confirmed H. pylori infection patients via stool antigen testing. Hemoglobin levels (men < 13 g/dL, women < 12 g/dL;); serum ferritin concentrations (men < 20 ng/mL, women < 10 ng/mL); diagnosis IDA. We performed statistical analyses, consisting of chi-square tests, to determine the association of IDA with patient demographics. Results: We identified 56 (24.6%) of 228 H. pylori infected patients with IDA. Hemoglobin mean 13.2 ± 1.9 g/dL and serum ferritin mean 24.2 ± 10.4 ng/dL. There was no statistically significant difference in IDA prevalence between males (26.6%) and females (22.1%; p = 0.432). IDA prevalence showed no significant effect by age stratification (p = 0.910). Conclusion: In fact, around one-fourth of patients with H. pylori infection had been observed to have IDA, which hinted at an association of the infection with iron metabolism disturbances. H. pylori infected individuals should receive routine screening for IDA to enable early intervention and better clinical outcomes. Work needs to be done to advance causal understanding and explore mechanisms. Keywords: Helicobacter pylori infection, Iron deficiency anemia, Gastritis, Hemoglobin, Serum ferritin.